Epistimology, Tarbiyah, talim, and Ta' dib in Reconstructing the Islamic Religious Education Curriculum and Ethics: Epistimologi, Tarbiyah, talim, dan Ta'dib dalam Rekonstruksi Kurikulum dan Etika Pendidikan Agama Islam - Sulwana, Siti; Riadi, Haris; Aswati, Fajar; Azlina, Azlina (Indonesian Journal of Innovation Studies, 2025)
General Background: Islamic education aspires to develop individuals who are both intellectually capable and morally grounded.Specific Background: Current implementations of the Islamic Religious Education (PAI) and Character curriculum often emphasize formal knowledge while underrepresenting integrative Islamic values. Knowledge Gap: There is limited curriculum design that holistically reflects Islamic epistemology by incorporating the classical concepts of ta’dīb, tarbiyah, and ta’līm. Aims: This study aims to formulate a reconstructed model for the PAI and Character curriculum based on Islamic epistemology by integrating these three foundational concepts. Results: Through a qualitative literature-based approach, this research identifies a three-domain framework: the value domain (ta’dīb), the process domain (tarbiyah), and the knowledge domain (ta’līm), aligned with the ideal of shaping an insān kāmil (perfected human). Novelty: The proposed model offers a comprehensive epistemological integration rarely seen in existing PAI curriculum frameworks. Implications: This study highlights the urgency of value reorientation in curriculum design and underlines the need for systematic teacher training to ensure effective implementation.  Highlights:  Integrates value, process, and knowledge domains rooted in Islamic thought. Aims to shape insān kāmil—a virtuous and knowledgeable human. Emphasizes teacher readiness for effective curriculum implementation. Keywords: Islamic Education Curriculum, Islamic Epistemology, Ta’dīb, Tarbiyah, Ta’līm